Types of National Values and their Importance in the Process of Educating Primary School Teachers - Xudaymurotovna, Xoʻshboqova Oysuluv (European Journal of Life Safety and Stability (2660-9630), 2022)
With the honor of our independence, it is one of the important tools to educate the young generation to be mature people in all respects by perfecting the values of our people, giving them a new meaning, expanding the effectiveness and sphere of influence of those that meet today’s requirements, forming a new worldview.